Acylated- and unacylated ghrelin during an oral glucose tolerance test in humans at risk for type 2 diabetes mellitus - Wolf, Magnus; Heni, Martin; Hennige, Anita M.; Sippel, Katrin; Cegan, Alexander; Higuita, Lina María Serna; Martus, Peter; Häring, Hans-Ulrich; Fritsche, Andreas; Peter, Andreas (International Journal of Obesity, 2023)
Background/Objectives The orexigenic peptide hormone ghrelin has been implicated in the pathophysiology of obesity and type 2 diabetes mellitus through its effects on nutrient homeostasis. Ghrelin is subject to a unique post-translational acyl modification regulating its biochemical activity. Subjects/Methods In this study we aimed to investigate the relation of acylated (AcG) as well as unacylated ghrelin (UnG) with body weight and insulin resistance in the fasting ( n = 545) and post-oral glucose tolerance test (oGTT) state ( n = 245) in a metabolically well characterized cohort covering a broad range of BMI (17.95 kg/m²–76.25 kg/m²). Results Fasting AcG (median 94.2 pg/ml) and UnG (median 175.3 pg/ml) were negatively and the AcG/UnG ratio was positively correlated with BMI (all p < 0.0001). Insulin sensitivity (ISI) correlated positively with AcG ( p = 0.0014) and UnG ( p = 0.0004) but not with the AcG/UnG ratio. In a multivariate analysis, including ISI and BMI, only BMI, but not ISI was independently associated with AcG and UnG concentrations. Significant changes of AcG and UnG concentrations were detectable after oGTT stimulation, with slight decreases after 30 min and increases after 90–120 min. Subject stratification into BMI-divergent groups revealed more pronounced AcG increases in the two groups with BMI < 40 kg/m². Conclusion Our data demonstrate lower concentrations for both AcG and UnG with increasing BMI as well as an increased proportion of the biologically active, acylated form of ghrelin giving point to pharmacologic intervention in ghrelin acylation and/or increase in UnG for treatment of obesity despite decreased absolute AcG levels.